A Pragmatics Analysis of Dark Humor In The End of The F***ing World Series - Shofa Hanin Assyifa; Misyi Gusthini (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
This study examines the characteristics of dark humor in the dialogues of the series The End of The F***ing World, directed by Jonathan Entwisle. Employing a pragmatic approach (Yule, 1996), Attardo’s (1994) General Theory of Verbal Humor (GTVH), and Grice’s (1975) theory of maxim violations, the study investigates how dark humor operates within character interactions. Dark humor is defined as a form of aggressive humor that derives amusement from taboo or sensitive subjects, often serving as both emotional release and social commentary. Data were collected from dialogues and analyzed using descriptive qualitative methods. The findings indicate that character interactions frequently feature hyperbolic and social dark humor to comment on extreme or socially sensitive situations, while deadpan and cynical humor conveys acceptance, resignation, and coping in stressful or unconventional circumstances. Pragmatically, these forms of dark humor serve multiple functions: they act as coping mechanisms, provide social commentary, and allow the expression of complex emotions, such as frustration, empathy, and resignation, in ways that are mutually understood within interactions but may appear ambiguous to outsiders. Overall, the study suggests that dark humor in the series functions not merely as entertainment but as a strategic communicative tool, enabling characters to manage emotional tension, navigate sensitive social issues, and reflect on social and psychological dimensions of their experiences.